Success Rate of Swept-Source Optical Coherence Tomography Biometry of Eyes of Elementary School Students - Tomita M; Yamashita T; Terasaki H; Yoshihara N; Kakiuchi N; Sakamoto T (Clinical Ophthalmology, 2022)
Masatoshi Tomita,* Takehiro Yamashita,* Hiroto Terasaki, Naoya Yoshihara, Naoko Kakiuchi, Taiji Sakamoto Department of Ophthalmology, Kagoshima University Graduate School of Medical and Dental Sciences, Kagoshima, Japan*These authors contributed equally to this workCorrespondence: Hiroto Terasaki, Department of Ophthalmology, Kagoshima University Graduate School of Medical and Dental Sciences, Kagoshima, Japan, Tel +81 99-275-5402, Fax +81 99-265-4894, Email teracchi@m2.kufm.kagoshima-u.ac.jpPurpose: To determine the success rate of swept-source optical coherence tomography (SS-OCT) biometry (OA-2000) in elementary school students.Methods: This was a prospective observational longitudinal study of 115 right eyes of elementary school students who were 8- to 9-years-old at the initial examination. Biometric measurements of the eyes were performed annually for three years, viz., during the third, fourth, and fifth grades. The success rates of obtaining data from optical biometric measurements of the axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), pupillary diameter (PD), corneal diameter (CD), and corneal curvature (CC) were determined.Results: The AL, CCT, and CC could be measured in all images at the three measurement times in all subjects. The success rate of the measurements of the ACD was 92.2% in the third grade and 100% in the fourth and fifth grade. The LT was successfully measured in 88.7% in the third grade, 99.1% in the fourth grade, and 100% in the fifth grade. The PD was successfully measured in 100% of the third grade, 96.0% of the fourth grade, and 100% in the fifth grade. The CD was successfully measured in 84.3% in the third grade, 66% in the fourth grade, and 100% in the fifth grade.Conclusion: SS-OCT can obtain accurate measures of all ocular parameters in the primary school students with high success rates. However, care should be taken especially in analyzing the ACD, LT, PD, and CD because errors can occur in some cases.Keywords: swept source optical coherence tomography, success rate, elementary school children